Menganalisis Financial Risk, Security Risk, Time and Convenince Risk dan Psichological Risk, Pada Perilaku Pembelian Online - Rahmi Rosita; Retno Setya Budiasningrum (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
This study aims to determine the effect of financial risk, security risk, time and convenience risk and psychological risk on consumer decision behavior to buy online. Questionnaires were distributed to 100 respondents who had purchased online at least twice in the last 3 months. The data analysis technique used is multiple linear regression analysis. The research found that risk is positively related to online consumer buying behavior. Risk or perceived by consumers is an important factor for online purchases. Security risk and financial risk must be low in order to get high and positive online buying behavior from online buying consumers. The smaller the risk the greater the purchase of online purchases. Risk Time and convenience show a positive relationship. The smaller the time risk and the perceived convenience, the greater the consumer's interest in making online purchases. Psychological risk shows a positive relationship to online purchases and shows that the role of the internet is getting bigger